The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1007/s11205-021-02647-1
|View full text |Cite
|
Sign up to set email alerts
|

How Gender-Based Disparities affect Women’s Job Satisfaction? Evidence from Euro-Area

Abstract: This paper analyses how gender-based disparities in the Euro-Area affect women's job satisfaction using the EWCS (2015), and the Global Gender Gap Index introduced by the World Economic Forum. Heckman's two-stage estimates show that women have a higher probability of job satisfaction than their male colleagues, which endorses the paradox of the female contented worker. There does not seem to be an equalization of job satisfaction as higher educational levels and lower age groups are considered. In those settin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
2
3
0
Order By: Relevance
“…The observed differences in satisfaction levels between male and female teachers regarding the TAGs program underscore the importance of considering gender as a relevant factor in PD studies. While these results resonate with previous research that has identified gender-based disparities in various areas of education (Fernández Puente & Sánchez-Sánchez, 2021), the nuances presented by this study deepen our understanding of how gender may impact the perceived impact and satisfaction of PD activities.…”
Section: Discussionsupporting
confidence: 88%
“…The observed differences in satisfaction levels between male and female teachers regarding the TAGs program underscore the importance of considering gender as a relevant factor in PD studies. While these results resonate with previous research that has identified gender-based disparities in various areas of education (Fernández Puente & Sánchez-Sánchez, 2021), the nuances presented by this study deepen our understanding of how gender may impact the perceived impact and satisfaction of PD activities.…”
Section: Discussionsupporting
confidence: 88%
“…This result is somewhat paradoxical as women’s working conditions are often inferior to those of their male counterparts, especially in terms of job segregation and salary. In any case, this result is not surprising in economic literature (Clark, 1997; Fernández Puente & Sánchez-Sánchez, 2021; Grönlund & Öun, 2018; Long, 2005; Perugini & Vladisavljevíc, 2019; Sousa-Poza & Sousa-Poza, 2007). It is noteworthy that this coefficient is higher in the public sector, as pointed out by Sánchez-Sánchez and Fernández Puente (2021).…”
Section: Resultssupporting
confidence: 64%
“…Indeed, our results are in line with the large strand of literature that suggests that women still feel more satisfied than men. Among others, Fernández Puente and Sánchez-Sánchez (2021) use the sixth EWCS and focus on the 19 countries of the European Monetary Union. Results on job satisfaction, which is measured by the question, ‘ I am enthusiastic about my job ’, show that, on average, women experience higher job satisfaction than men.…”
Section: Discussionmentioning
confidence: 99%